The Influence of Environmental, Social, Governance (ESG) Disclosure on Firm Value: Mediating Role of Earning Quality - La'bi', Melihana Bilang; Daromes, Fransiskus Eduardus (Magister Akuntansi - Universitas Atma Jaya Makassar, 2025)
This study aims to investigate the effect of environmental, social, governance (ESG) disclosure as a mechanism to improve firm value through earnings quality as a mediator. This study uses stakeholder theory as the main theory and signal theory as a supporting theory. This study uses secondary data in the form of annual reports and sustainability reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The number of samples was 109 company data for 3 years, which was selected using the purposive sampling method. The results of this study show that ESG disclosure has a positive and significant effect on earnings quality. Earnings quality has a positive but not significant effect on firm value. ESG disclosure has a positive and significant effect on firm value. In addition, earnings quality do not play a role in mediating the relationship between ESG disclosure and firm value.